A comprehensive assessment on bioavailability, leaching characteristics and potential risk of polycyclic aromatic hydrocarbons in biochars produced by a continuous pyrolysis system. (January 2022) - Shen, Xiuli; Meng, Haibo; Shen, Yujun; Ding, Jingtao; Zhou, Haibin; Cong, Hongbin; Li, Lijie
Abstract: Biochar application as a soil amendment has attracted worldwide attention. Nevertheless, polycyclic aromatic hydrocarbons (PAHs) formed during biochar production might enter into ecosystems and threaten human health after application to soil. Continuous pyrolysis systems tend to cause an accumulation of PAHs in biochar owing to short residence time and rapid cooling. This study conducted a comprehensive assessment regarding potential risk of PAHs in biochars produced by a continuous pyrolysis system based on bioavailability, leaching behavior, toxic equivalent quantity, health risk and phytotoxicity of PAHs. Results showed that the concentrations of total PAHs in biochars were in the range of 93.40–172.40 mg/kg, exceeding the European Biochar Certificate standard. 3-rings PAHs were the predominant groups. The percentages of total freely dissolved and leachable PAHs were lower than 1%. RH contained the least bioavailable and leachable PAHs concentration and phytotoxicity compared with CS and PS, which might attribute to the characteristic of three biochars. CS and PS were acidic and exhibited high levels of DOC and VFAs, while RH was strongly alkaline and presented greater aromaticity and higher surface area, which might have resulted in high adsorptive capacity and decreased bioavailability of PAHs. When the biochar application rate was higher than 0.6 t/ha, the incremental lifetime cancer risk value for human exposure to biochar-borne PAHs through the biochar-amended soil was over 10 −6, suggesting carcinogenic risks. Germination index values of biochars ranged from 25.66 to 88.95%. Phytotoxicity mainly was caused by bioavailable PAHs and dissolved organic compounds. Overall, these findings highlighted that although the percentage of bioavailable PAHs was low, the potential health risk and phytotoxicity of PAHs in biochars produced by a continuous pyrolysis system was of a great concern. High biochar application rates should be avoided without processing both for soil safety and human health. Graphical abstract: Image 1 Highlights: Biochars contain high levels of PAHs, exceeding EBC threshold values. 3-ring PAHs were predominated in the three crop residues biochars. PAHs associated with the three biochars exhibited low bioavailability. The maximum safe application rates of biochars were <0.6 t/ha in view of cancer risk. CS and PS posed phytotoxicity with GI values < 80%.